Neural Stem Cells: Exogenous and Endogenous Promising Therapies for Stroke - Guerra-Crespo, M.; Herrán-Arita, A.K. De la; Boronat-García, A.; Maya-Espinosa, G.; García-Montes, J.R.; Fallon, J.H.; Drucker-Colín, R. (IntechOpen, 2012)
None